Sustainable Recovery in Health Tourism: Managerial Insights from a Mediterranean Destination during the COVID-19 Pandemic - Erkanli, Emine; Kilic, Hasan; Ozturen, Ali (Mdpi, 2024)
Health tourism, a sector that has gained increasing global attention, particularly in the context of sustainable development, is poised for significant growth even in the face of the COVID-19 pandemic. This study investigates the challenges faced by the health tourism sector in a small Mediterranean country, focusing on sustainable recovery strategies. The current study aims to determine managerial implications post-COVID-19, emphasizing sustainability in operational practices and long-term demand growth. We conducted in-depth interviews with 32 health tourism managers and experts, and the qualitative content analysis with Leximancer identified key themes such as sustainable demand management, organizational adaptation, and crisis recovery. This study revealed eight critical themes related to managerial survival and the demand for sustainable practices in health tourism, namely demand, hotel, tour operators, employees, crises, social media, word of mouth, and time. These findings underscore the importance of integrating sustainability into tourism recovery strategies, ensuring long-term resilience for the industry. This study, which provides theoretical and practical insights into the sustainable growth of health tourism amidst global crises, serves as a valuable reference for stakeholders seeking sustainable development solutions, inspiring them to contribute to the sector's growth.
Keywords: health tourism; sustainability; COVID-19; recovery; sustainable development